The ‘Oceanic feeling’ in Stephen Crane’s The Open Boat and S.T. Coleridge’s The Rime of the Ancient Mariner - Doroholschi, Claudia Ioana (Review of International American Studies, 2014)
Claudia Ioana Doroholschi West University of Timisoara, Romania Stephen Crane’s ‘The Open Boat’ (1897) is a fictionalized account of the writer’s experience of surviving the shipwreck of the Commodore, a steamboat on which he was heading for Cuba to act as a war correspondent. The present paper will explore Crane’s account of the encounter between man and sea, setting it against the background of S.T. Coleridge’s ‘Rime of the Ancient Mariner’, which Crane’s story echoes on several occasions. I will examine the two texts in the light of the concept of ‘oceanic feeling’, as defined by Romain Rolland and Sigmund Freud, who both use the metaphor of the ocean as a site of the sublime to speak of a sense of oneness, of connectedness between man and world. I will argue that, while in Coleridge’s poem the Mariner first loses and subsequently recovers a mystical connection with nature, embodied by the connection between man and sea, in Crane’s story the situation is more complex. The short story echoes ‘The Rime of the Ancient Mariner’ at key points in the plot, but seems to decode the events in a psychological rather than mystical key. Thus, it seems to suggest that a sense of oneness with nature is not the result of any transcendent connection between man and his surroundings, but merely a projection of the subject’s emotions onto an indifferent ature—thus suggesting a psychological reading more consistent with Freud’s than with Rolland’s notion of oceanic feeling. Crane’s emphasis on an absurd and indifferent nature in ‘The Open Boat’ has often been read as typical of literary Naturalism. However, I will argue that the ending of the story suggests a return to the Romantic/Rollandian oceanic feeling, and will attempt to untangle the mechanisms and reasons for this reversal. I will also try to account for the allusions to ‘The Rime of the Ancient Mariner’ in this context.